Long-Term Safety of Tofacitinib for Treatment of Moderate-to-Severe Ulcerative Colitis: Three Years of Korean National Data - Song, Eun Mi; Seo, Gi Hyeon; Jung, Sung Hoon (Journal of Korean medical science, 2025)
Ulcerative colitis (UC) requires long-term treatment. Tofacitinib, a JAK inhibitor approved for UC, raises safety concerns regarding serious adverse events (SAEs) such as thromboembolism, major adverse cardiovascular events (MACEs), and opportunistic infections. This study aimed to evaluate the long-term safety of tofacitinib versus anti-tumor necrosis factor (TNF) inhibitors in Korean patients with UC using a nationwide population-based cohort. We analyzed data from the National Health Insurance Service database from May 2019 to April 2022. Patients with UC were identified using the International Classification of Diseases, 10th revision and rare intractable disease codes. We compared the incidence of SAEs, including MACE, thromboembolic events, herpes zoster, tuberculosis, and malignancy, between the tofacitinib and anti-TNF inhibitor groups. The risk factors for SAEs in all patients with UC and tofacitinib users were also analyzed. A total of 1,816 patients with UC were included (521 treated with tofacitinib and 1,295 treated with anti-TNF inhibitors). The overall incidence of SAEs was similar between the tofacitinib and anti-TNF inhibitor groups (4.41/100 person-years vs. 5.33/100 person-years, = 0.332). Thromboembolic events, including MACE, pulmonary thromboembolism, and deep vein thrombosis, were comparable between the two groups ( = 0.151). The incidence of opportunistic infections (herpes zoster and tuberculosis) and malignancy did not differ significantly between the two groups. Among tofacitinib users, older age (≥ 60 years) and concomitant hypertension were significant risk factors for SAEs. Tofacitinib demonstrates a safety profile comparable to that of anti-TNF inhibitors in Korean patients with UC. Despite safety concerns, tofacitinib can be safely used in this population with caution in older patients and those with comorbidities.